Performance of the Supplementary Feeding Program in the Prevention and Management of Stunting in East Medan Sub-District - Ichwani Rezeki Nasution; Audia Junita; Yanhar Jamaluddin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Stunting is a chronic nutritional problem that inhibits children's physical growth and cognitive development, especially in the first 1,000 days of life. This condition has a long-term impact on the quality of human resources and future productivity. This study aims to analyze the performance of the East Medan Sub-district Government in implementing the Supplementary Feeding Program (PMT) as a specific intervention for stunting prevention and handling. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation studies. The results showed that the prevalence of stunting in Medan Timur Sub-district decreased from 15.04% in 2022 to 11.29% in 2024. However, there was a decrease in the number of PMT beneficiaries from 528 people in 2022 to 460 people in 2024, indicating challenges in program planning and distribution. Performance analysis based on Dwiyanto's (2008) five indicators shows that program productivity and accountability are good, but service quality, responsiveness, and efficiency still require improvement.